The single supervisory mechanism - Panacea of quack banking regulation? Preliminary assessment of the evolving regime for the prudential supervision of banks with ECB involvement - Tobias H. Tröger (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2013)
This paper analyzes the evolving architecture for the prudential supervision of banks in the euro area. It is primarily concerned with the likely effectiveness of the SSM as a regime that intends to bolster financial stability in the steady state. By using insights from the political economy of bureaucracy it finds that the SSM is overly focused on sharp tools to discipline captured national supervisors and thus underincentives their top-level personnel to voluntarily contribute to rigid supervision. The success of the SSM in this regard will hinge on establishing a common supervisory culture that provides positive incentives for national supervisors. In this regard, the internal decision making structure of the ECB in supervisory matters provides some integrative elements. Yet, the complex procedures also impede swift decision making and do not solve the problem adequately. Ultimately, a careful design and animation of the ECB-defined supervisory framework and the development of inter-agency career opportunities will be critical. The ECB will become a de facto standard setter that competes with the EBA. A likely standoff in the EBA's Board of Supervisors will lead to a growing gap in regulatory integration between SSM-participants and other EU Member States. Joining the SSM as a non-euro area Member State is unattractive because the current legal framework grants no voting rights in the ECB's ultimate decision making body. It also does not supply a credible commitment opportunity for Member States who seek to bond to high quality supervision.
urn:nbn:de:hebis:30:3-315503; More recent version: http://hdl.handle.net/10419/146952
Keywords: G21; G28; H77; K22; K23; L22; 330; prudential supervision; banking union; regulatory capture; political economy of bureaucracy; Single Supervisory Mechanism (SSM); European Central Bank (ECB); European Banking Authority (EBA)